Analisa Faktor-Faktor Penyebab Kecemasan Pasien pada Pemeriksaan MRI (Magnetic Resonance Imaging) - Irma Rahmania (Poltekkes Kemenkes Semarang, 2021)
Background: The existence of MRI (Magnetic Resonance Imaging) in every hospital is not widely known by the general public or patients, especially about the benefits and importance of MRI (Magnetic Resonance Imaging) for radiological supporting examinations. The problem with this examination revolves around its management, especially the indication that requires an MRI examination, the patient tends to have a perception with a little excessive concern that leads to the finding of abnormal examination results.Research methods: The research design used was descriptive qualitative with an observational analytic approach. The technique of determining the sample using a cross-sectional formula. With a sample size of 90 patients who underwent MRI examinations. Data obtained from literature study, observation, documentation, and questionnaires. Data analysis used bivariate with chi square method and multivariate with multiple regression test.Result: Chi square and multivariate bivariate analysis with multiple regression test. The results showed that there was a significant relationship between age and education level variables.Conclusion: Of the three variables tested, there are 2 factors that have a relationship with the patient's anxiety level, namely the age and education level of the patient.